Lambton's alloy lining. (Reprint series (Nickel Development Institute (Canada)), 1994)
After completing 50 km of welds to install 270 tonnes of nickel-alloy sheet at the Lambton thermal generating plant, Ontario Hydro's first flue-gas desulphurization project is expected to start up this summer.